The Difficulty Level of Online Learning in The Remote Areas during The New Normal Period (NOBEL: Journal of Literature and Language Teaching, 2023)
Online learning still occurs in many places during the New Normal, along with limited face-to-face learning. However, offline learning in several regions had to be withdrawn because of the new version of the coronavirus. One platform of online learning that is often used is Google Classroom. This study aims to determine the difficulty level of online learning with Google Classroom in STKIP Pamane Talino students in the new normal period. To reach the aim of the study, the researchers used a qualitative descriptive method. Fifty-nine students in the Extensive Reading class of second-semester students of the English Education Study Program, STKIP Pamane Talino, were selected to participate in this study. The data analysis technique used in this study was critical analysis. The data were collected through observation and interviews. The questionnaire results showed that 73% of the respondents agreed with the ease of using the Google Classroom application in online learning, which can be categorized as good. From the result above, it can be suggested that online learning using Google Classroom is one of the alternative ways to online learning in remote areas during the new normal period.